Evaluating Machine Tool Alternatives Through Modified TOPSIS And Alpha-Cut Based Fuzzy ANP - Ayağ, Zeki; Özdemir, Rifat Gürcan (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2012)
The problem of machine tool selection among available alternatives has been critical issue for most companies in fast-growing markets for a long time. In the presence of many alternatives and selection criteria, the problem becomes a multiple-criteria decision making (MCDM) machine tool selection problem. Therefore, most companies have utilized various methods to successfully carry out this difficult and time-consuming process. In this work, both of the most used MCDM methods, the modified TOPSIS and the Analytical Network Process (ANP) are introduced to present a performance analysis on machine tool selection problem. The ANP method is used to determine the relative weights of a set of the evaluation criteria, as the modified TOPSIS method is utilized to rank competing machine tool alternatives in terms of their overall performance. Furthermore, in this paper, we use a fuzzy extension of ANP, a more general form of AHP, which uses uncertain human preferences as input information in the decision-making process, because AHP cannot accommodate the variety of interactions, dependencies and feedback between higher and lower level elements. Instead of using the classical eigenvector prioritization method in AHP, only employed in the prioritization stage of ANP, a fuzzy logic method providing more accuracy on judgments is applied. The resulting fuzzy ANP enhances the potential of the conventional ANP for dealing with imprecise and uncertain human comparison judgments. The proposed approach is also applied for a real-life case in a company. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: multiple criteria decision making; analytic network process; fuzzy ANP; machine tool selection; çok kriterli karar verme; analitik ağ süreci; bulanık ANP; tezgah seçimi